Data and Its Increasing Importance among Organizations and Businesses - José Miguel Orellana Parapi; Edi Sunjayanto Masykuri (Scripta : English Department Journal, 2020)
Data is a driving factor in our current society, its presence is in each simple and complex system holding important insights and clues that can lead to a better performance; although its importance people usually tend to ignore its potential of discovering and organizing unusual and interesting patterns and connections within. The “Big data” era provides us with a stable and huge ground to support modern business and analytics models, which may impact directly the way how we perceive present actions and spotting possible future tendencies, improving and enhancing current decision models. This paper tries to highlight some of the various uses and strategies that several organizations are given to their databases and their data structures, and describing some of the most salient and widespread achievements made by the correct use and manipulation of a data warehouse; moreover, a revision to some syllabus of major universities and colleges were analyzed to detect tendencies on the way how professional are being formed regarding to managing data and its corresponding analysis